Ulnar Tunnel Syndrome-3 Case Reports - Matsumoto, Masanori; Chosa, Etsuo; Nakamura, Seiji; Tajima, Naoya; Toda, Masaru (Orthopedics & Traumatology, 1993)
The ulnar tunnel syndrome is a relatively uncommon consition resulting from compression of the ulnar nerve as it passes through the ulnar in the wrist. We have experienced 3 cases of ulnar tunnel syndrome during 10 years. The syndrome may cause weakness and atrophy of the intrinsic hand muscles and loss of sensation in the distribution of the ulnar nerve. Two patients (Case 1 and 2) had muscle weakness and sensory impairment. One patient (Case 3) had muscle weakness and no sensory disturbance. The causes were truma (Case 1), lipoma (Case 2) and ganglion (Case 3). Electromyographic study is important in assessing the involved in diagnosing a space occupying lesion in the ulnar tunnel.